Marker and readout genes for defense priming in Pseudomonas cannabina pv. alisalensis interaction aid understanding systemic immunity in Arabidopsis - Andrea J. Sistenich; Lisa Fürtauer; Franziska Scheele; Uwe Conrath (Scientific Reports, 2024)
Abstract Following localized infection, the entire plant foliage becomes primed for enhanced defense. However, specific genes induced during defense priming (priming-marker genes) and those showing increased expression in defense-primed plants upon rechallenge (priming-readout genes) remain largely unknown. In our Arabidopsis thaliana study, genes AT1G76960 (function unknown), CAX3 (encoding a vacuolar Ca2+/H+ antiporter), and CRK4 (encoding a cysteine-rich receptor-like protein kinase) were strongly expressed during Pseudomonas cannabina pv. alisalensis-induced defense priming, uniquely marking the primed state for enhanced defense. Conversely, PR1 (encoding a pathogenesis-related protein), RLP23 and RLP41 (both encoding receptor-like proteins) were similarly activated in defense-primed plants before and after rechallenge, suggesting they are additional marker genes for defense priming. In contrast, CASPL4D1 (encoding Casparian strip domain-like protein 4D1), FRK1 (encoding flg22-induced receptor-like kinase), and AT3G28510 (encoding a P loop-containing nucleoside triphosphate hydrolases superfamily protein) showed minimal activation in uninfected, defense-primed, or rechallenged plants, but intensified in defense-primed plants after rechallenge. Notably, mutation in only priming-readout gene NHL25 (encoding NDR1/HIN1-like protein 25) impaired both defense priming and systemic acquired resistance, highlighting its previously undiscovered pivotal role in systemic plant immunity.